2017
DOI: 10.5798/dicletip.339004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Self-Efficacy of Adolescents with Chronic Health Conditions

Abstract: Objective: Chronic Health Conditions (CHC) and problems among adolescents have recently become more frequent. CHC may have an influence on their perception of quality of life and self-efficacy. This research aimed to compare quality of life and self-efficacy among adolescents with CHC and without CHC.Methods: The research was conducted with 778 adolescents from a high school. Students were asked as follows: "Have you had any health condition which requires a doctor supervision and/or which requires continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…This notion has been also supported by Caprara, Steca, Gerbino, Pacielloi and Vecchio (2006) who stated that perceived selfefficacy foster positive expectations about the future, to retain a high self-concept, to perceive life satisfaction and to experience more positive emotions. Other researchers have confirmed that adolescents' self-efficacy beliefs have positive effects on psychological well-being (Moeini et al, 2008;Tommasi et al, 2018), subjective well-being (Ma, Zeng & Ye, 2015;Yap & Baharudin, 2016) and quality of life (Taş, Öztürk-Çopur, Ünlü, Tüzün, & Özcebe, 2017). Telef and Ergün (2013) found, on sample composed by 311 Turkish adolescents, that academic, social, and emotional self-efficacy beliefs predicted their subjective well-being.…”
Section: Self-efficacymentioning
confidence: 90%
“…This notion has been also supported by Caprara, Steca, Gerbino, Pacielloi and Vecchio (2006) who stated that perceived selfefficacy foster positive expectations about the future, to retain a high self-concept, to perceive life satisfaction and to experience more positive emotions. Other researchers have confirmed that adolescents' self-efficacy beliefs have positive effects on psychological well-being (Moeini et al, 2008;Tommasi et al, 2018), subjective well-being (Ma, Zeng & Ye, 2015;Yap & Baharudin, 2016) and quality of life (Taş, Öztürk-Çopur, Ünlü, Tüzün, & Özcebe, 2017). Telef and Ergün (2013) found, on sample composed by 311 Turkish adolescents, that academic, social, and emotional self-efficacy beliefs predicted their subjective well-being.…”
Section: Self-efficacymentioning
confidence: 90%
“…Individual interviews during follow‐ups revealed that many of the adolescents who were attending school delayed or did not take their medication at all during school times, and would be reluctant to mention their disease. In another study, adolescents with chronic diseases were reported to have a poorer quality of life in school functioning (Taş et al, 2017). Likewise, the emotional status of adolescents can have a significant effect on the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Benzer olarak Taş ve ark. 'nın (28) ergenlerde yaptığı çalışmada, kronik hastalığı olan adölesanların okul ile ilgili olarak yaşam kalitesi puanları düşük bulunmuştur.…”
Section: Introductionunclassified